KARAKTERISTIK RUMAH TANGGA PENGGUNA AIR MINUM KEMASAN DAN ISI ULANG DI INDONESIA - Elsa Elsi; Sahat P Manalu; Dasuki Dasuki; Aria Kusuma (Puslitbang Upaya Kesehatan Masyarakat, 2018)
ABSTRACT One of SDG's 2030 targets is that households have access to drinking water. The phenomenon is some of community use bottled water/refill as drinking water. The aim of this article are knowing household proportion with improve clean water source and water collecting time that use bottled water/refill drinking water, and relation of clean water source characteristics with using bottle/refill drinking water. Research design is cross sectional. Dependent variable is household drinking water sources type, independents are household clean water source characteristics, and travel time collecting water. Bivariate data analysis was carried out to analyze the relationship between the proportion of bottled / refilled water users by households with adequate water sources and households that use inappropriate water sources. The results showed that proportion of households with unimproved drinking water sources, unimproved clean water source and unimproved water collecting time are greater using bottled/refill drinking, each (7,6%) and (26,7%). There are statistic significances relation between household with unimproved drinking water source, unimproved travel time collecting water with using bottled/ relill drinking water (p = 0,000). Also found statistic significances between household with improved drinking water source, unimproved clean water source and unimproved travel time collecting water with using bottled/ relill drinking water (p = 0,000). Keywords: Bottled water, refill drinking water, improved water ABSTRAK Salah satu target SDG’s 2030 adalah rumah tangga memiliki akses terhadap air minum. Sebagian masyarakat menggunakan air minum kemasan/ isi ulang sebagai air minum. Artikel ini bertujuan untuk mengetahui karakteristik pengguna air minum kemasan/isi ulang sebagai sumber air utama. Desain penelitian adalah potong lintang. Variabel terikat adalah jenis sumber air minum rumah tangga, sedangkan variabel bebas terdiri dari karakteristik sumber air utama dan waktu yang diperlukan untuk mengambil air. Analisis data secara bivariat dilakukan untuk menganalisis hubungan antara proporsi pengguna air minum kemasan/isi ulang oleh rumah tangga dengan sumber air layak dengan rumah tangga yang menggunakan sumber air tidak layak. Hasil menunjukkan bahwa proporsi pengguna air minum kemasan/isi ulang oleh rumah tangga dengan sumber air minum yang belum layak lebih tinggi diibandingkan dengan rumah tangga dengan sumber air minum layak, yaitu masing-masing (7,6%) dan (26,7%). Terdapat hubungan bermakna antara rumah tangga dengan sumber air minum belum layak, dengan waktu tempuh pengambilan air belum layak terhadap penggunaan air minum kemasan/ isi ulang (p=0,000). Pada rumah tangga dengan sumber air minum layak, sumber air utama belum layak dan waktu pengambilan belum layak juga ditemukan hubungan bermakna secara statistik terhadap penggunaan air minum kemasan/ isi ulang (p=0,000). Kata kunci: Air kemasan, air minum isi ulang, air layak